Self-organizing models of bacterial aggregation states - Manuela Caratozzolo; Santina Carnazza; Luigi Fortuna; Mattia Frasca; Salvatore Guglielmino; Giovanni Gurrieri; Giovanni Marletta (Mathematical Biosciences and Engineering)
In this work, aggregation states of bacteria on engineered surfacesare investigated both from the experimental point of view and from the theo-retical one. The starting point of this work is a series of experiments carried outon abiotic surfaces in which bacteria adhere forming self-organized patterns.To reproduce the main characteristics of the phenomenon a model based onself-organization of a group of agents has been used. The agents represent bac-teria and are free to move on a given surface. On the basis of local rules theymay adhere and then eventually form self-organized aggregates. Our numericalresults demonstrate that few simple rules are able to explain the emergence ofself-organized patterns. Depending on the parameters used, the model is ableto reproduce the aggregation patterns observed under different experimentalconditions and to predict the behavior of a culture of two bacterial species.